Synthesis and Electrochemical properties of metal(II)- carboxyethylphenylphosphinates - Bazaga-García, Montse; Vílchez-Cózar, Álvaro; Maranescu, Bianca; Olivera-Pastor, Pascual; Marganovici, Marko; Ilia, Gheorghe; Cabeza-Díaz, Aurelio; Visa, Aurelia; Pérez-Colodrero, Rosario Mercedes (Royal Society of Chemistry, 2021)
We report herein the synthesis, structural characterization and electrocatalytic properties of three new coordination polymers, resulting from the combination of divalent metal (Ca2+, Cd2+ or Co2+) salts with (2-carboxyethyl)(phenyl)phosphinic acid. In addition to the usual hydrothermal procedure, the Co2+ derivative could be also prepared by microwave-assisted synthesis, in much shorter times. The crystal structures were solved ab initio, from powder diffraction data. Compounds MII[O2P(CH2CH2COOH)(C6H5)]2 {M= Cd (1) or Ca (2)} crystallize in the monoclinic system and display a layered topology, with the phenyl groups pointing toward the interlayer space in a interdigitated fashion. Compound Co2[(O2P(CH2CH2COO)(C6H5)(H2O)]2·2H2O (3) presents a 1D structure composed of zig-zag chains, formed by edge-sharing cobalt octahedra, with phenyl groups pointing outside. Packing of these chains is favored by hydrogen bond interactions via lattice water. In addition, H-bonds along the chains are established with participation of the water molecules and the hydrophilic groups from the ligand. However, the solid exhibits a low proton conductivity, attributed to the isolation of the hydrophilic regions caused by the arrangement of hydrophobic phenyl groups. Preliminary studies on the electrocatalytical performance for the oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) have been conducted for compound 3 and its pyrolytic derivatives, which were previously throughout characterized. By comparison, another Co2+ phosphinate, 4, obtained by microwave-assisted synthesis, but with distinct stoichiometry and known structure was also tested. For OER, the best performance was reached with a derivative of 3, prepared by heating this compound in N2 at 200 °C. This derivative presented overpotential (339 mV, for a current density of 10 mA·cm-2) and Tafel slope (51.7 mV·dec-1) values comparable to other Co2+ related materials.
https://doi.org/10.1039/D1DT00104C
Keywords: Electroquímica; Protones; Electrochemical properties; proton conductivity; metal(II)-carboxyethylphenylphosphinates